2013
DOI: 10.1371/journal.pone.0064611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renal Sympathetic Denervation on Atrial Substrate Remodeling in Ambulatory Canines with Prolonged Atrial Pacing

Abstract: We have previously demonstrated that catheter-based renal sympathetic denervation (RSD) could suppress atrial fibrillation (AF) in canines with short-time rapid right atrial pacing (RAP). However, the role of renal denervation on atrial remodeling is unclear. The aim of the present study was to explore the long-term effect of RSD on the atrial remodeling during prolonged RAP. Twenty mongrel dogs were implanted with a high-frequency cardiac pacemaker with a transvenous lead inserted into the right atrial append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 44 publications
(59 reference statements)
0
49
0
Order By: Relevance
“…18 The effect of RDN on the development of an atrial structural remodeling and AF has not been investigated sufficiently. 19 In particular, the influence of RDN on the complexity of AF propagation patterns, 20 representing the functional consequence of atrial structural remodeling, 21,22 has not yet been studied. This study is aimed to determine the effect of sympathetic nervous system modulation by RDN on structural and neural remodeling in the atrium and AF complexity in a goat model of persistent AF without hypertension or structural heart disease.…”
mentioning
confidence: 99%
“…18 The effect of RDN on the development of an atrial structural remodeling and AF has not been investigated sufficiently. 19 In particular, the influence of RDN on the complexity of AF propagation patterns, 20 representing the functional consequence of atrial structural remodeling, 21,22 has not yet been studied. This study is aimed to determine the effect of sympathetic nervous system modulation by RDN on structural and neural remodeling in the atrium and AF complexity in a goat model of persistent AF without hypertension or structural heart disease.…”
mentioning
confidence: 99%
“…Therefore, RDN may be an effective therapy for management of ventricular arrhythmia because RDN can regulate renin‐angiotensin‐aldosterone system activation and sympathetic activity 14, 15. Our study demonstrated that VF inducibility was higher in VPC rabbits than that in control rabbits.…”
Section: Discussionmentioning
confidence: 60%
“…The impact of RDN on atrial remodeling and AF inducibility caused by right atrial pacing has also been studied in a dog model [25]. During programmed stimulation chronic right atrial pacing group dogs exhibited higher numbers of AF inducements compared to sham group.…”
Section: Impact Of Rdn On Atrial Electrophysiology and Atrial Arrhythmentioning
confidence: 99%
“…During programmed stimulation chronic right atrial pacing group dogs exhibited higher numbers of AF inducements compared to sham group. Moreover, it was indicated that RDN could suppress atrial remodeling induced by right atrial pacing [25]. On the other hand, in a pig model investigators showed that increased AF inducibility after atrial tachypacing was not changed by RDN while AF cycle length after 30 minutes of atrial tachypacing 10 was decreased compared with baseline and not further modulated by RDN [26].…”
Section: Impact Of Rdn On Atrial Electrophysiology and Atrial Arrhythmentioning
confidence: 99%